Viabilidade do recipiente biodegradável na produção de mudas florestais nativas - Viégas, Lucas Bertacini [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The most used containers to forest seedlings production are derivative from petroleum, however, new alternatives that cause less impact on the environment have became accepted in the industry coupled with the rational use of irrigation water. In this perspective, the purpose of this study was to assess the technical and economic viability of the biodegradable container (Ellepot®) comparing it with the polyethylene container in the production of tree seedlings of the species Schinus terebinthifolius, Handroanthus vellosoi and Esenbeckia leiocarpa under three water management. The experiment was conducted from February to December 2013 in the experimental nursery of the Department of Forest Science in Botucatu-SP. Each species was characterized as a research composed of two experiments, the first with a shorter cycle of days (indicated for the biodegradable container) and the other with a larger cycle (indicated for the polyethylene container). The experiments were set up in a 2x3 factorial, corresponding to two containers: polyethylene and biodegradable, and three daily gross irrigation blades (8, 11 and 14 mm). Technical analysis consisted of morphological evaluations and initial development of seedlings in pots. The economic analysis included production costs, considering all the inputs used, capital cost, depreciation of the infrastructure and of the equipment used and the production cycle. To Shinus terebinthifolius in both production cycles, shoot height variables, stem diameter, dry mass (aerial, root and total), height / diameter relationship and Dickson Quality Index were higher in plants with biodegradable container, where the 14 mm blade had the best results. ToHandroanthus vellosoi, in both cycles, all variables were higher in seedlings with biodegradable container, where the 11 mm blade had the best results of the first cycle, and 14 mm blade to the second cycle. Esenbeckia leiocarpa was ...

Os recipientes mais utilizados para produção de mudas florestais são derivados de petróleo, porém, novas alternativas que causam menor impacto ao ambiente vêm ganhando espaço no setor, aliado ao uso racional da água de irrigação. Nesta perspectiva, o objetivo deste estudo foi avaliar a viabilidade técnica e econômica do recipiente biodegradável (Ellepot®) comparando-o com recipiente de polietileno na produção de mudas das espécies Schinus terebinthifolius, Handroanthus vellosoi e Esenbeckia leiocarpa sob três manejos hídricos. O experimento foi conduzido de fevereiro a dezembro de 2013 no viveiro experimental do Departamento de Ciência Florestal em Botucatu-SP. Cada espécie caracterizou-se como uma pesquisa composta por dois experimentos, sendo o primeiro com ciclo menor de dias (indicado para o recipiente biodegradável), e outro com ciclo maior (indicado para o recipiente de polietileno). Os experimentos foram dispostos no esquema fatorial 2x3, correspondendo a dois recipientes: polietileno e biodegradável, e três lâminas brutas diárias de irrigação (8, 11 e 14 mm). A análise técnica foi composta por avaliações morfológicas e desenvolvimento inicial das mudas em vasos. A análise econômica contemplou os custos de produção, ponderando todos os insumos utilizados, custo de capital, depreciação da infraestrutura e dos equipamentos utilizados e o ciclo de produção. Para Schinus terebinthifolius, em ambos os ciclos de produção, as variáveis altura da parte aérea, diâmetro do colo, massas secas (aérea, radicular e total), relação altura/diâmetro e Índice de Qualidade de Dickson foram maiores nas mudas com recipiente biodegradável, sendo a lâmina de 14 mm com os melhores resultados. Para Handroanthus vellosoi, ambos os ciclos, todas as variáveis foram maiores nas mudas com recipiente biodegradável, sendo a lâmina de 11 mm com os melhores resultado ...
Biodegradable container viability on the production of native forest tree seedlings
Keywords: Viveiros florestais; Manejo da irrigação; Arvores - Mudas - Recipientes; Análise econômico-financeira; Viveiros de mudas; Nursey stock